2021
DOI: 10.1007/978-3-030-77442-4_45
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Adjust Effort Estimation of Function Point Analysis

Abstract: This study presents a modified approach to adjust a software development effort estimation. The AdamOptimizer-based regression model is adopted to adjust and enhance the accuracy of effort estimation. This approach is derived into three phases. The first step deals with the logarithmized formula of effort estimation computed by Function Point Analysis and Productivity Delivery Rate. The Adam-Optimizer-based regression model is examined in the second phase, and the ISBSG repository 2020 release R1 is considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In 2021, Hoc et al [26] developed the Adj-Effort method to optimize effort estimates in terms of FPA on the basis of the ISBSG version 2020. In order to get the most accurate estimate possible, they used a method called MLR based on AdamOptimizer [10] with 10-fold cross-validation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Hoc et al [26] developed the Adj-Effort method to optimize effort estimates in terms of FPA on the basis of the ISBSG version 2020. In order to get the most accurate estimate possible, they used a method called MLR based on AdamOptimizer [10] with 10-fold cross-validation.…”
Section: Related Workmentioning
confidence: 99%
“…We used 10-fold cross-validation to compare different adaption strategies. The primary reason is because 10-fold cross-validation has been used in prior research and is suggested by [4], [26], and [27] for comparing effort estimate models.…”
Section: Threats To Validitymentioning
confidence: 99%
“…Casper-Jones presented a rule (5) that might be the suitable solution to measure the software effort in the project's early stages when the productivity value is unknown [25]. It will be used as a baseline model for comparison.…”
Section: Table 2 General Systems Characteristicsmentioning
confidence: 99%
“…We used the 10-fold crossvalidation strategy to compare various adaptation techniques. The main reason is that 10-fold cross-validation has previously been used in studies and is recommended by [18], [25], and [29] for comparing effort estimation models.…”
Section: Threats To Validity a Internal Threatsmentioning
confidence: 99%